(-3分之2m+n)(-3分之2n-m))
1个回答
(-3分之2m+n)(-3分之2n-m))
= - 9 分之 (2m+n) x (2n-m )
= - 9 分之 (2mn+2n²-2m²-mn)
= - 9 分之 (mn+2n²-2m²)
相关问题
已知2m+n分之m-2n=3,则2m+n分之3(m-2n)+3(2m+n)分之m-2n-4(2m+n)分之5(m-2n)
已知2m+n分之m-2n=3,求代数式2m+n分之3m-6n减3(2m+n)分之m-2n-m-2n分之5(2m+n)
|m+2n分之2m-n|=3,求m+2n分之2(2m-n)-m+2n分之2m-n-3的值?
m+2n分之2m-n的绝对值=3,求m+2n分之2(2m-n)-m+2n分之2m-n-3
m+2n分之2m-n的绝对值=3,求m+2n分之2(2m-n)-m+2n分之2m-n-3的值
3分之m+n-4分之n-m=2 4m+3分之2=8
如果m+n=2又3分之1,m-n=3又2分之1,则4(n-m)=( ).2-7分之3m-7分之3n=( ).
已知n分之m-n=2分之3,求n分之3m+2n的值
当2m+n分之2m-n=3时,则代数式2(2m-n)分之3(2m+n)减去3(2m+n)分之2(2m-n)的值是多少?(
方程组 2分之m+3分之n=13 3分之m-4分之n=3